An integrated flood risk assessment approach based on coupled hydrological-hydraulic modeling and bottom-up hazard vulnerability analysis. (February 2022) - Zhang, Ke; Shalehy, Md Halim; Ezaz, Gazi Tawfiq; Chakraborty, Arup; Mohib, Kazi Mushfique; Liu, Linxin
Abstract: Accurately quantifying and assessing the flood risks is critical for flood hazard mitigation and prevention. This study proposed a new integrated flood risk assessment framework to map flood risk, hazard and vulnerability by coupling the HEC-HMS hydrological model, the HEC-RAS 1D and 2D hydraulic models, and a bottom-up hazard vulnerability analysis. The Old Brahmaputra River floodplain of Bangladesh, a flood-prone region, was chosen as a case study. The coupled hydrological-hydraulic model shows a comparable robust performance in both calibration and validation periods with Nash-Sutcliffe efficiency coefficient = 0.93 (0.81), coefficient of determination = 0.95 (0.89), and percent bias = −1.17% (2.40%) for the calibration (validation) period. Our results indicate that the assessed risk levels are roughly consistent with the overall property distribution and flood-hazard potential in the study area. The proposed framework and associated findings are valuable for developing adaptation strategies and early-warning systems to reduce flood impacts in the future. Highlights: Developed an integrated flood risk assessment framework to map flood risk, hazard and vulnerability. Coupled the HEC-HMS hydrological model, the HEC-RAS hydraulic models, and a bottom-up hazard vulnerability analysis. Mapped flood risks of the flood-prone Old Brahmaputra River floodplain of Bangladesh. Provided a used modeling system for flood adaptation and early-warning.